2015
DOI: 10.2494/photopolymer.28.739
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Practicality of Melanin as a Photodynamic-Inactivation Photosensitizer by Its Nanonization

Abstract: It has been proposed that melanin may play a role in the antimicrobial defense system of a human body. Furthermore, it has been found that melanin has efficacy against oxidative stress, tumor, venin, virus, and heavy metal ions. In view of the great potential of melanin in medical applications revealed by its photodynamic actions, we develop techniques based on mechanical stir and photo-fragmentation with femtosecond laser pulses respectively for nanonization of melanin to produce nanometer-sized and water-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Although some properties and effects caused by pheomelanin nanoparticles have been investigated in previous works [1,25,38], there is not reported evidence about its inactivation action in bacteria. Due to the fact E. coli is Gram-negative, its photoinactivation is a challenging aim.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some properties and effects caused by pheomelanin nanoparticles have been investigated in previous works [1,25,38], there is not reported evidence about its inactivation action in bacteria. Due to the fact E. coli is Gram-negative, its photoinactivation is a challenging aim.…”
Section: Final Remarksmentioning
confidence: 99%
“…The authors found a reduction of around 50% of viability. In another study, Yi-Cheng et al [38] investigated the effect of Sepia and synthetic melanin in Gram-positive bacteria irradiated at 660 nm, reporting non-significant response.…”
Section: Introductionmentioning
confidence: 99%